Architectural excellence : in a diverse world culture - Baker, William T. (Victoria : Images Publishing Dist Ac, 2008)
Provides a unifying theory for architectural design with a decidedly culturally neutral approach.
Keywords: Architectural design; Architectural design--Philosophy